Pengaruh Lama Penjemuran terhadap Kadar Air, Penyusutan, Keempukan, dan Akseptabilitas pada Urutan Daging Domba - Pramudya, Calvin Gilang; Suryaningsih, Lilis; Gumilar, Jajang (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Urutan is one of Bali's traditional fermented sausage products made from meat and pork fat mixed with Balinese spices, then stuffed into pig intestine casings. Drying is one of the stages in making urutan products which aims to make spontaneous fermentation. This study aimed to determine the effect of drying time and the best drying time on water content, shrinkage, tenderness, and acceptability of lamb meat urutan. This research was conducted experimentally using a Completely Randomized Design (CRD) with 3 treatments (P1 = 2 days drying time, P2 = 4 days drying time, P3 = 6 days drying time) and 6 repetitions. Data on water content, shrinkage, tenderness were analyzed using the variance test and Duncan's further test while the acceptability data were tested using Kruskal-Wallis and Mann-Whitney further test. The results showed that the effect of drying time on the order of lamb meat showed a significant effect on water content, shrinkage, tenderness and acceptability to taste. Duration of drying 2 days is the best treatment to be used in lamb meat urutan with a water content of 49,13%; shrinkage of 14,45%; tenderness of 56,18 mm/gram/second; and favored by panelists.